Respostas fisiológicas, crescimento e compostos bioativos de cultivares de beterraba em sistemas de cultivo solteiro e consorciado com coentro no verão - Oliveira, Francisco Ronaldo Alves de (2023)
Beetroot (Beta vulgaris L.) is native to regions with mild climates and its cultivation is difficult in places with high temperatures and solar radiation, especially in summer. Under these conditions, the intercropping system can favor the production of agricultural crops. The objective of this study was to evaluate the agronomic characteristics, biological efficiency, postharvest quality, physiological responses, and bioactive compounds of five beetroot cultivars intercropped with coriander (Coriandrum sativum) in summer. The study was carried out between December 2020 and February 2021, in an area of the Federal University of Ceará, in Fortaleza-CE. Five beetroot cultivars (Itapuã 202, Early Wonder 2000, Early Wonder Tall Top, Fortuna, and Maravilha) intercropped with coriander were evaluated. A randomized block design with four replicates was used. The beetroot was harvested 72 days after sowing (DAS). During this period, two coriander cultivation cycles were carried out, with harvests at 37 and 32 DAS. Biometric and productive characteristics of beetroot and coriander were evaluated; biological efficiency indexes of intercropped systems; post-harvest quality parameters, gas exchange and bioactive compounds of beetroot. The productivity of commercial roots of beetroot cultivars in the single system was higher than that in the intercropped system, with averages of 14.54 and 6.32 t ha -1, respectively. The productivity of fresh biomass of coriander in the single system was higher than that in the intercropped system with beetroot (20.41 and 9.10 t ha -1 , respectively), with the first cycle being superior to the second. Only the Fortuna cultivar in intercropped system had a land use efficiency index (LUE) greater than 1.0, while Early Wonder 2000 and Early Wonder Tall Top had better system productivity indexes (SPI). The cultivars Itapuã 202, Early Wonder Tall Top and Maravilha had a higher soluble solids/titratable acidity ratio compared to the cultivars Early Wonder 2000 and Fortuna. The cultivars had a lower percentage of white rings in the intercropped crop, with the exception of Fortuna, which had a lower percentage in the single crop. The cultivars Early Wonder 2000, Early Wonder Tall Top and Maravilha had better performance in net photosynthetic rate (A), instantaneous carboxylation efficiency (iCE) and instantaneous water use efficiency (WUE) at 36 DAS in single crop. At 69 DAS, the Early Wonder Tall Top had higher A, iCE and WUE in both cropping systems, together with the Early Wonder 2000 in intercropped crop. Higher total polyphenol content was observed in the cultivars Early Wonder 2000, Early Wonder Tall Top and Maravilha in the intercropped system. The Fortuna cultivar had a higher content of total betacyanins and betalains, while Early Wonder 2000, Early Wonder Tall Top and Maravilha had a higher content of betaxanthins. The single cultivation of coriander and the beet cultivars Itapuã 202, Early Wonder 2000, Early Wonder Tall Top and Maravilha is more advantageous than the intercropping system, while Fortuna has greater biological efficiency in intercropping with coriander. The intercropping system improves the quality of beet roots by decreasing the percentage of concentric white rings and increasing the total polyphenol contents. Intercropping limits beet gas exchanges at 36 DAS and favors them at 69 DAS.